Pathology of uterus cavity in women with and without postmenopausal bleedings in correlation with time since last menstrual period and gynaecological history - Słodki, Maciej; Juchnowicz-Bierbasz, Romuald; Smuklerz-Kajdos, Elżbieta; Jędrzejczyk, Sławomir (Menopause Review/Przegląd Menopauzalny, 2007)
Objective: The aim of the study was to assess the frequency of different uterus cavity pathology in women with and without bleeding after menopause in correlation with time since last menstrual period. Material and methods: We analyzed 181 women after dilatation and curettage procedure because of bleeding after menopause or because of abnormal endometrium in transvaginal sonography. Results: During the first 5 years after menopause in women without bleeding the most common pathology were was endometrial polyps; otherwise in women with bleeding the most common was hyperplasia endometrium without atypia. There was no hyperplasia with atypia and cancer in the group of women without bleeding during the first 5 years after menopause. In both groups the most common pathology between 6 and 14 years after menopause were was endometrial polyps. In women more than 14 years after menopause without bleeding we found one case of cancer and hyperplasia with atypia. In women more than 14 years after menopause with bleeding we found hyperplasia with atypia in 22% and endometrial cancer in 8% of women. Conclusions: 1. There was no correlation between the kind and or frequency of pathology in uterine cavity and number of pregnancypregnancies, deliveries, abortions, and or age of first and last menstrual period. 2. In all subgroups of women with bleeding after menopause the most common pathology was endometrial hyperplasia and with time since menopause there was increased frequency of hyperplasia with atypia and endometrial cancer. 3. In all subgroups of patients without bleeding after menopause the most common pathology were was endometrial polyps; overall whole numberfrequency of hyperplasia decreased with time since menopause but in at the same time increase the frequency of hyperplasia with atypia increased.